A study of mhd fluid with second order slip and thermal flow over a nonlinear stretching sheet - Jauhri, Shefali; Mishra, Upendra (Zielona Góra: Uniwersytet Zielonogórski)
An electrically conducted viscous incompressible nanofluid flow caused by the nonlinear stretching surface with stagnation flow has been investigated numerically. The effect of Brownian motion and thermophoresis on the nanofluid is also incorporated. The governing partial differential equations with nonlinear second order boundary conditions are solved by the fourth order Runge-Kutta technique using MATLAB programming. The effect of the radiation parameter (Rd), stretching parameter (n), Brownian motion parameter (Nb), thermophoresis parameter (Nt) on temperature, velocity and mass transfer are shown graphically.
Keywords: stagnation point flow; second order slip boundary conditions; nonlinear stretching sheet; Runge-Kutta method